(untitled) (KULT_online, 2017)
In recent years, the histories of child welfare and children’s charities have been enriched by other historiographical developments, such as new imperial history, cultural history or the history of the globalizing processes. Thereby, historians have reassessed cultural constructions of childhood by examining the ways in which politicians, social reformers, philanthropists and scientists have attempted to make use of poor and (supposedly) needy children at home and abroad in order to further their respective political and social projects. This essay discusses three recent books that, by studying specific aspects of child welfare in nineteenth-century Britain and the United States, deal with the political, social, and cultural dimensions of child welfare and its development in national, imperial, and global contexts. This essay, moreover, discusses how the authors, examining a broad range of historical records (such as sources from welfare institutions, state archives, philanthropic journals, promotional literature, and oral history interviews, etc.), explore both the discourses on children and childhood as well as practices of child care that led to the formation of private and public welfare politics for geographically near and/or distant children in changing social and political contexts.